Ultrasonographic Analysis of Optimal Needle Placement for Extensor Indicis - Jin Young Kim; Hyun Seok; Sang-Hyun Kim; Yoon-Hee Choi; Jun Young Ahn; Seung Yeol Lee (Annals of Rehabilitation Medicine, 2020)
Objective To determine the most optimal needle insertion point of extensor indicis (EI) using ultrasound. Methods A total 80 forearms of 40 healthy volunteers were recruited. We identified midpoint (MP) of EI using ultrasound and set MP as optimal needle insertion point. The location of MP was suggested using distances from landmarks. Distance from MP to medial border of ulna (MP-X) and to lower margin of ulnar head (MP-Y) were measured. Ratios of MP-X to Forearm circumference (X ratio) and MP-Y to forearm length (Y ratio) were calculated. In cross-sectional view, depth of MP (Dmp), defined as middle value of superficial depth (Ds) and deep depth (Dd) was measured and suggested as proper depth of needle insertion. Results Mean MP-X was 1.37±0.14 cm and mean MP-Y was 5.50±0.46 cm. Mean X ratio was 8.10±0.53 and mean Y ratio was 22.15±0.47. Mean Dmp was 7.63±0.96 mm. Conclusion We suggested that novel optimal needle insertion point of the EI. It is about 7.6 mm in depth at about 22% of the forearm length proximal from the lower margin of the ulnar head and about 8.1% of the forearm circumference radial from medial border of ulna.